THE PROCESS OF USING THE MODEL TO PROMOTE A MULTICULTURAL SOCIETY WITH COMMUNITY PARTICIPATION NATHAB MODEL TO RAISE AWARENESS OF CITIZENSHIP OF SOCIETY IN NATHAB SUBDISTRICT CHANA, DISTRICT, SONGKHLA PROVINCE - Suwanno, Pitchaya; Churak, Yuwanda; Boonrat, Arisra; Suksang, Saisuda; Aeksaitharn, Chittaphon (Journal of Social Science and Cultural, 2023)
This research aims to study the process of bring a pattern strengthening a multicultural society with community participation (Nathab Model). Go and try it out with a model community and evaluation used of model the Nathab Model. The sample used in this research is people in the area Nathab Subdistrict, Chana District, Songkhla Province. Classified into 2 groups is the sample group for collecting qualitative data of 60 persons and quantitative data of 392 persons. The tools used in this research were in-depth interviews and evaluation questionnaires. Statistics used were percentage, mean and standard deviation. The findings of the study reveal that. The process of applying the Nathab Model to community has 6 steps: 1) Organize a meeting of partners in cooperation networks. 2) Consider drafting an annual event calendar and good stuff Nathab. 3) Determine an action plan for pilot activities Nathab Subdistrict. 4) Set up an annual activity calendar and good stuff Nathab. 5) Organize a pilot project is "Annual event in Nathab Subdistrict (Khong de 4 Chay)”. 6) Evaluate and summarize the results of the pilot project. As for the evaluation used of the Nathab Model, it was found that people of Nathab Subdistrict there are opinions on the Nathab Model for promoting a multicultural society with community participation (Nathap Model) on the issue of the model development process and operations using the Nathab Model Overall at a highest level that with an average of 4.02. Considering each issue: was obtained from the project matched expectations with the highest mean equal to 4.20 Followed by the issue Spatial data is used to Develop a suitable format The mean was 4.12 Participation issues in proposing ideas and guidelines for the development of the Nathab Model is consistent with the way of life of the people in Nathap Subdistrict with an average of 4.04, respectively.